(untitled) (Yupana, 2020)
This paper describes the analysis of a lesson proposal implemented in 6th grade of primary education. The objective of this proposal is to address the teaching from the interdisciplinary, breaking times and spaces, moving away from the fragmentation of contents. To this end, the methodology adopted is project-based learning (ABP), since it promotes student research, and with it the skills required by this century are promoted. Likewise, statistical education is exposed as a transversal axis for the teaching of other sciences, in which the ABP is presented as the ideal strategy. For the approach described, the theoretical foundations that support the proposal are presented first, and then a description of each work day with the students and their respective analysis is made. Finally, the conclusions of the work are presented with their weaknesses, strengths and possible modifications.